Planet Janet - Sheldon, Dyan (Candlewick, 2003)
Sixteen-year-old Janet Bandry keeps a diary as she deals with an annoying family, school, a quirky best friend, and trying to find herself through vegetarianism, literature, romance, and her "Dark Phase."